1985
DOI: 10.1002/1097-0142(19850315)55:6<1398::aid-cncr2820550639>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surgical margins and prognostic factors predicting the risk of local recurrence in 3445 patients with primary cutaneous melanoma

Abstract: Risk factors associated with local recurrences were analyzed from a series of 3445 clinical Stage I melanoma patients. In single‐factor analysis, tumor thickness, ulceration, and increasing age were highly significantly predictive of recurrence (p < 0.00001). After 5 years of follow‐up, local recurrence rates were 0.2% for tumors less than 0.76 mm thick, 2.1% for tumors 0.76 to 1.49 mm thick, 6.4% for tumors 1.5 to 3.99 mm thick, and 13.2% for tumors 4.0 mm or greater in thickness. Ulcerated melanomas recurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
1
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(104 citation statements)
references
References 28 publications
1
100
1
2
Order By: Relevance
“…A total of 7 subsequent CMs comprised 5 local recurrences (including satellite metastases and in-transit melanoma metastases), 1 distant metastasis, and 1 second primary melanoma. The incidence of local recurrence was 3.1%; this was consistent with previous studies that reported a local recurrence rate of approximately 3%∼5% [13][14][15] . The prevalence of a second primary melanoma following a primary CM was 0.6%; this was similar than the prevalence of 0.5%∼5.5% reported by previous studies [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7 subsequent CMs comprised 5 local recurrences (including satellite metastases and in-transit melanoma metastases), 1 distant metastasis, and 1 second primary melanoma. The incidence of local recurrence was 3.1%; this was consistent with previous studies that reported a local recurrence rate of approximately 3%∼5% [13][14][15] . The prevalence of a second primary melanoma following a primary CM was 0.6%; this was similar than the prevalence of 0.5%∼5.5% reported by previous studies [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…In these statistics, the term "recurrence" may indicate local recurrence, regional metastasis, and/or distant metastasis or all of these. The incidence of local recurrence is estimated to be 3-5% in some studies [2,12,13]. and these recurrences usually present within 5 years after diagnosis of the primary melanoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the current case, none of these patients experienced local recurrences in the same site more than once. Studies and reviews of local recurrence by Urist, Cohn-Cedermark, Dong, and Heenan did not include late recurrences [2,13,15,16]. Another study by Crowley, et al, reported 18 patients with local recurrence after at least 10 years of disease free interval, but the follow up information on local recurrence was grouped with regional node and in-transit recurrence and thus this data was excluded from our review [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the sign of aggressive biology that leads to distant metastatic disease and implies a poor prognosis in over 80% of cases [43]. The head-neck region, in particular, is associated with a greater risk of local recurrence, and a worse prognosis [44].…”
Section: Discussionmentioning
confidence: 99%